2013
DOI: 10.2298/vsp1310903s
|View full text |Cite
|
Sign up to set email alerts
|

Fatal pulmonary thromboembolism after prolonged physical immobilization in hospitalized psychiatric patients

Abstract: Our results suggest a possible link between prolonged physical immobilization of psychiatric patients who also receive antipsychotic therapy, and total PTE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…The patient was not submitted to hormone testing, nor determining the value of prolactin. Increased risk of venous thrombosis in fixed patients, has already been described, usually after a period of 3-5 days fixation, which corresponds to our cases in who the period of fixation was 5 days 8,9 . Some authors suggest high doses of antipsychotics and quiescence as a cause of pulmonary thromboembolism in psychiatric patients in the intensive care unit 10 .…”
Section: Discussionsupporting
confidence: 87%
“…The patient was not submitted to hormone testing, nor determining the value of prolactin. Increased risk of venous thrombosis in fixed patients, has already been described, usually after a period of 3-5 days fixation, which corresponds to our cases in who the period of fixation was 5 days 8,9 . Some authors suggest high doses of antipsychotics and quiescence as a cause of pulmonary thromboembolism in psychiatric patients in the intensive care unit 10 .…”
Section: Discussionsupporting
confidence: 87%
“…Asphyxia caused by strangulation was mentioned in 10 studies [Refs. (40, 43, 45, 46, 53, 56, 57, 69, 73, 78), the latter one reporting a patient in seclusion crawling into the bed sheets] and pulmonary embolism in eight studies (41, 42, 49, 51, 64, 68, 71, 74). Other causes were suicide [Ref.…”
Section: Resultsmentioning
confidence: 99%
“…The second most frequently analyzed harm was VTE in 14 studies: deep vein thrombosis of the leg (DVT) in 8 studies (18, 22, 38, 39, 41, 51, 70, 72) and pulmonary embolism (PE) in 12 studies (38, 39, 41, 42, 49, 51, 64, 68, 70–72, 74), with the consequence of death in 8 studies (41, 42, 49, 51, 64, 68, 71, 74). Gaertner et al (38) retrospectively found out that among the analyzed patients with VTE, the restrained patients were not more frequently affected by this harm than the unrestrained.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations